The Effect Of Effleurage Massage and Slow Stroke Back Massage Reduce Menstrual Pain Intensity - Indriyani Makmun; Rizkia Amalia; Ana Pujianti Harahap; Ni Wayan Ari Adiputri; Catur Esty Pamungkas (Midwifery and Nursing Research, 2023)
Background: Menstrual pain is the pain arising before or along with menstruation, lasting for a few hours and can last up to several days. Effleurage massage is doing by rubbing gently, not giving strong pressure and pressing fingertip in the skin surface slowly. Slow stroke back massage is a gentle, slow, any rhythmic massage in the back by covering 5 cm area on both sides of the spine bulge from head to the sacrum area. This study aims to determine the difference of effectiveness effleurage massage and slow stroke back massage to reduce menstrual pain intensity in the students of University of Muhammadiyah Mataram in 2020. Methods: The design of this study was quasy experiments with two group pretest-posttest design. The population was the entire students Permata Husada Midwifery Academy, there were two groups, namely efflurage and slow stroke back massage group with 16 students each by using purposive sampling technique. Results: The results of the research showed the mean of pain intensity for the efflurage group is 18,94 while for the backrub massage 14,06 even there is significant differences according to pvalue. P value is > 0,05.